2014
DOI: 10.5433/1679-0359.2014v35n1p317
|View full text |Cite
|
Sign up to set email alerts
|

Physical properties of snacks made from cassava leaf flour

Abstract: The food industry is continually growing with new products becoming available every year. Extrusion combines a number of unit operations in one energy efficient rapid continuous process and can be used to produce a wide variety of snacks foods. The objective of this study was to evaluate the effect of extrusion temperature, screw speed, and amount of cassava leaf flour mixed with cassava starch on the physical properties of extruded snacks processed using a single screw extruder. A central composite rotational… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 16 publications
1
9
0
Order By: Relevance
“…LEONEL et al (2009) observed similar behavior in extrudates from cassava starch. EI is a quality indicator; the more expanded products tend to be the more crisp they will be, which increases consumer market acceptability (FERRARI et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…LEONEL et al (2009) observed similar behavior in extrudates from cassava starch. EI is a quality indicator; the more expanded products tend to be the more crisp they will be, which increases consumer market acceptability (FERRARI et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Extrusion is a cooking process for a short time at high temperature, in which a combination of mechanical shear action, heat and humidity resulting in a molecular rearrangement besides other chemical reactions, giving the processed product special and diversified characteristics (FERRARI et al, 2014). During extrusion process, a whole series of changes take place in the raw material such as starch and protein hydration, homogenization, starch gelatinization, protein denaturation, destruction of anti-nutritional factors and microbial load reduction (VERNAZA et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…This is an indication that the sample has the highest mineral content, a contribution by the cassava leaves and the groundnut used as fortificant. It has been established that cassava leaves have a higher ash content than cassava roots and other leafy vegetables (Ferrari et al, 2014;Karri & Nalluri, 2016). Some cassava leaves varieties have been found to have as high as 4.5% ash content (Montagnac et al, 2009).…”
Section: Nutritional Properties Of Fortified and Non-fortified Cassava Leaves Saucementioning
confidence: 99%
“…In some countries, cassava leaves are considered as a poor man's food and only eaten when other vegetable leaves are unavailable, or during food shortage and in several countries, they are not consumed at all (Latif & Müller, 2015). In Brazil, for instance, a large amount of cassava leaves is wasted during root harvest, and it has been estimated that for an area of 158 million hectares, more than 178,000 tons of leaves are wasted each year (Ferrari et al, 2014). It is possible to obtain approximately 2,250 kg of cassava leaf flour per hectare, depending on the quantity of leaves produced per plant per hectare (Sagrilo et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Despite high levels of protein, fiber, minerals and vitamins, cassava leaves contain cyanide, a toxic substance that prevents their consumption "in natura" (FERRaRI et al, 2014). Democratic Republic of Congo is the most import producer of cassava leaves with an estimated production of 85,007 tons (Fao, 2014).…”
Section: Food Technologymentioning
confidence: 99%